Representation of Bisexuality in F.C. Yee’s Avatar: The Rise of Kyoshi - Abdurrafi Nugraha Putra (Fakultas Ilmu Budaya, 2026)
This research analyzes how bisexuality is depicted in novels using Hall's theory of representation. This study is also supported by Sedgwick's theory of homosocial desire, which serves to categorize homosocial and homosexual data. The purpose of this study is to find out how bisexuality is represented in novels and to find out the reasons why novelists include this element in novels aimed at young adults. To obtain these answers, the researcher collected data related to bisexuality found in conversations, scenes, and narratives in the novel. It was found that bisexuality was depicted by the characters Kyoshi (female), Rangi (female), and Yun (male). From this representation, it was found that Kyoshi had a relationship with Yun, which can be categorized as Kyoshi's heterosexual phase. Then, Kyoshi entered a homosocial phase with her friend Rangi. After an intense romantic relationship, Kyoshi and Rangi's relationship developed into a homosexual phase. It should be noted that Kyoshi came from the Earth Kingdom, which was inspired by the Chinese monarchy. In the Wanli period (1573-1620) during the Ming dynasty, homosexuality was somewhat accepted in society. This can be interpreted as Kyoshi's homosexuality being a reflection of the Chinese monarchy era. To find out the reason why the author included bisexuality in the novel, the researcher collected data in the form of an interview between the author and a journalist. The reason the author of the novel included this element was simply because Kyoshi's bisexuality had already been hinted at in the vii sequel The Legend of Korra: Turf Wars, which was released two years before Avatar: The Rise of Kyoshi. F.C. Yee, as the author, did not intend to promote LGBT issues through his work. Yee said that he was only continuing something that had previously only been a hint.
Reuploud file repositori 19 Mei 2026_Firli Validasi file repositori 15 Juni 2026_Firli
Keywords: Theory of Representation; Bisexuality; The Rise of Kyoshi; Novel Analysis